Routing selection algorithm with considering the queuing delay for system protection communication network - Chuan LIU; Zaichao HUANG; Jing TAO; Huibin JIA (Dianxin kexue)
Currently,a fast and reliable transmission path was calculated by routing algorithm that satisfies the system protection communication network under the requirements of delay and reliability,without considering that when the grid fails or the traffic in the network is excessive,the queuing delay of many nodes in the communication network will greatly increase.Aiming at this problem,a routing algorithm was proposed to solve the minimum queuing delay and improve the real-time performance of wide area protection.Experimental results show that the total information delay of the path calculated by the routing algorithm proposed is the smallest under the requirements of system protection reliability.